Biological sex is associated with heterogeneous responses to IL-6 receptor inhibitor treatment in COVID-19—A retrospective cohort study - Dan F. Stein; Conor Foley; Matt Byott; Eleni Nastouli; Gareth Ambler; Nishkantha Arulkumaran (Scientific Reports, 2023)
Abstract COVID-19 is associated with higher inflammatory markers, illness severity and mortality in males compared to females. Differences in immune responses to COVID-19 may underpin sex- specific outcome differences. We hypothesised that anti-IL-6 receptor monoclonal antibodies are associated with heterogenous treatment effects between male and female patients. We conducted a retrospective cohort study assessing the interaction between biological sex and anti-IL-6 receptor antibody treatment with respect to hospital mortality or progression of respiratory failure. We used a Cox proportional hazards regression model to adjust for age, ethnicity, steroid use, baseline C-reactive protein, and COVID-19 variant. We included 1274 patients, of which 58% were male and 15% received anti-IL-6 receptor antibodies. There was a significant interaction between sex and anti-IL-6 receptor antibody use on progression to respiratory failure or death (p = 0.05). For patients who did not receive anti-IL-6 receptor antibodies, the risk of death was slightly higher in males (HR = 1.13 (0.72–1.79)), whereas in patients who did receive anti-IL-6 receptor antibodies, the risk was lower in males (HR = 0.65 (0.32–1.33)). There was a heterogenous treatment effect with anti-IL-6 receptor antibodies between males and females; with anti-IL-6 receptor antibody use having a greater benefit in preventing progression to respiratory failure or death in males (p = 0.05).